Adolescents' perspective on the networking business. - Babiano, Arbeth A. (Arbeth Babiano, 2011)
The study explored the perceptions of networking business from the perspectives of adolescents, the reasons why they engage and do not engage and the effects or results when they engage and do not engage in the said business. Seventy five adolescents whose ages are from 16 to 21 years old were the respondents of the study, identified purposively. The results were gathered through an interview schedule of 75 respondents to determine the adolescents' perception on networking business, the reasons why they engage and do not engage and the effects or results when they engage and do not engage in networking business. Results showed that the common perceptions of adolescents on networking business are business-building people and money, achieving goals and dreams, providing opportunities, big income-earning big, leadership-helping and convincing people, scam, requires more time and effort-demanding, and risky. Meanwhile, the results showed that reasons why adolescents engage in networking include helping the family, meeting new friends, earning big income, curiosity and experience, and financial freedom. On the other hand, reasons why adolescent do not engage in networking business are having no time, busy, many priorities, afraid to invite, not interested at all, requires much time, and effort and far too risky. Results also showed that the common effects of networking business to adolescents are changed lives, financial freedom, awareness, personal growth, confusion, and contributed knowledge.